PENGARUH SELF-EFFICACY TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA PESERTA DIDIK KELAS XII SMA NEGERI 2 PONTIANAK - Asy Sifa Safarina; Halida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the effect of self-efficacy on theinterest in continuing education to college in class XII students atSMA Negeri 2 Pontianak. Self-efficacy, as an individual's belief intheir ability to undergo academic tasks, is expected to influencestudents' decisions to continue their education. The research methodused was quantitative with descriptive design, involving 94respondents selected through random sampling technique. Datawere collected using a questionnaire that measured the level of Self-efficacy and interest in continuing education. Based on the results ofthe calculation, the average Self-efficacy of students is in the highcategory with a percentage of 78.82%. Meanwhile, interest incontinuing education to college is also high, reaching 81.46%.Simple linear regression test indicates that there is a significantinfluence between Self-efficacy and interest in continuing education,with a significance value of 0.001. This finding confirms thatstrengthening self-efficacy can be an important strategy inincreasing students' interest in continuing their studies to a higherlevel.